Smart money? Philanthropic and federal funding for the Common Core - Kornhaber, Mindy L.; Barkauskas, Nikolaus J.; Griffith, Kelly M. (Education Policy Analysis Archives, 2016)
The Common Core State Standards Initiative seeks to prepare all students to graduate high school without remedial needs, to improve transparency across states’ accountability systems, and to foster efficiencies in the development and distribution of educational resources. The reform was adopted in more than 40 states and has been described as state-led. We examined federal and philanthropic funding for the reform through a conceptual lens of resource dependence theory. Our document analyses surfaced eight pathways along which funding for the Common Core traveled into, through, and around the public education system. We consider clusters of pathways according to their purposes and the consequences of such clustering for the reform. We conclude by discussing benefits derived from this funding for different types of entities that grant and receive it.